Constructed wetlands for water quality improvement (Lewis Publishers, 1993)
Constructed Wetlands for Water Quality Improvement is a virtual encyclopedia of state-of-the-art information on the use of constructed wetlands for improving water quality. Well-organized and easy-to-use, this book features contributions from prominent scientists and provides important case studies. It is ideal for anyone involved in the application of constructed wetlands in treating municipal and industrial wastewater, mine drainage, and non-point source pollution. Constructed Wetlands for Water Quality Improvement is a "must" for industrial and municipal water treatment professionals, consulting engineers, federal and state regulators, wetland scientists and professionals, ecologists, environmental health professionals, planners, and industrial environmental managers.